Three-Dimensional Mandibular Condyle Remodeling Post-Orthognathic Surgery: A Systematic Review - Zygimantas Petronis; Audra Janovskiene; Jan Pavel Rokicki; Dainius Razukevicius (Medicina)
Background and Objectives: The most popular surgical procedures among orthognathic surgeries for Class II and III patients are Le Fort 1 osteotomy for the maxilla and bilateral sagittal split ramus osteotomy (BSSRO) for the mandible. Keeping the condyle in its proper place during fixation is one of the difficulties of orthognathic surgery. One of the worst post-orthognathic surgery consequences in the temporomandibular joint (TMJ) area may be condylar resorption. Condylar remodeling refers to a group of processes that occur in reaction to forces and stress placed on the temporomandibular joint in order to preserve morphological, functional, and occlusal balance. A systematic review of the literature was performed with the aim of identifying the mandibular condylar component of TMJ changes after orthognathic surgery in class II and III patients. Materials and Methods: An electronic search was carried out using the PubMed, Cochrane Library, and Google Scholar, databases. The inclusion criteria included trials in non-growing patients upon whom orthognathic surgery was performed due to Angle II or Angle III classes malocclusion; in addition, a CT or cone beam computed tomography (CBCT) scan was performed before and after surgery to track the mandibular condylar component of TMJ changes. The quality of the studies was evaluated by two independent authors. The risk of bias was assessed by using the Downs and Black checklist. Results: The electronic and manual literature search yielded 12 studies that fulfilled all necessary inclusion criteria. Observed studies were evaluated as good (3), fair (8), and poor (1) quality. Two studies evaluated class II patients, six studies observed class III patients, and four studies were comparative. Most of the studies evaluated condyle angle and space changes, and the condylar surface and volume changes were also observed. However, the methodology of evaluation in the publications differs. Conclusions: Reduction of bone density, especially in class II patients, and morphological condyle reshaping, with the apposition of the bone, is the main adaptive mechanism after orthognathic surgery. However, all of the studies we examined were conducted using different methods of evaluation, measurement, and reference points.